ANALISIS FILM SYAMIL DODO SERTA RELEVANSINYA DENGAN MATA PELAJARAN FIKIH MATERI RUKUN ISLAM DI MI - Irfan Nurhamzah; Asis Saefuddin; Muhammad Sofyan (Magistra)
This study aims to determine the educational values of worship contained in the Syamil and Dodo films, as well as the relevance of the Syamil and Dodo films to fiqh subjects, the material of the pillars of Islam, which can later be used as teaching materials in teaching the material of the pillars of Islam to students, so that in addition to understanding the Islamic law itself, students can also deepen their understanding. This study employs a semiotic method in conjunction with a qualitative approach. The author gathers information from the selected Syamil and Dodo films in order to identify the signs in each episode. The study’s findings indicate that the film Syamil and Dodo contains educational worship values, specifically worship of mahdhah and worship of ghair mahdhah. Furthermore, the episode Pengertian Dua Kalimat Syahadat, Doa dan Shalat, Rukun Shalat, Shalat Berjamaah, Macam-macam Zakat, Zakat dan Hukumnya, Adab Puasa, Keutamaan Ramadhan, Hukum Haji dan Manasik Haji in the film Syamil and Dodo has relevance to fiqh subjects on material Pillars of Islam